Effect of immigration on multiple sclerosis sex ratio in Canada: the Canadian Collaborative Study. Issue 1 (25th August 2009) - Orton, S-M; Ramagopalan, S V; Brocklebank, D; Herrera, B M; Dyment, D A; Yee, I M; Sadovnick, A D; Ebers, G C
Abstract : Background: The ratio of female to male (F:M) multiple sclerosis (MS) cases varies geographically, generally being greater in areas of high prevalence. In many regions, including Canada, rising MS incidence in women has been implied by the marked increase in F:M ratio. Methods: We examined the F:M ratio over time in MS patients in the Canadian Collaborative Study born outside Canada, with onset postmigration (n = 2531). We compared the trends to native-born Canadians, by region of origin and age at migration. Results: Regression analysis showed that year of birth (YOB) was a significant predictor of sex ratio in immigrants (χ 2  = 21.4, p<0.001 correlation r = 0.61). The rate of change in sex ratio was increasing in all migrant subgroups (by a factor of 1.16 per 10-year period, p<0.001), with the steepest increase observed in those from Southern Europe (1.27/10 years, p<0.001). The overall immigrant F:M ratio was 2.17, but varied by country of origin. It was significantly lower in migrants from Southern Europe compared with Northern Europe or USA (1.89 vs 2.14 and 2.86, p = 0.023 and p = 0.0003, respectively). Increasing age at immigration was associated with decreasing sex ratio (p = 0.041). The sex ratio of individuals migrating <21 was significantly higher than those migrating ⩾21 (2.79 vs 1.96, p = 0.004). Conclusions: MS sex ratio in immigrants to Canada is increasing but variable by region of origin and influenced by age at migration. The findings highlight the importance of environmental effect(s) in MS risk, which are likely gender-specific.